PENGARUH DISIPLIN KERJA, KOMPENSASI, JAM KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI STRES KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PERDAGANGAN KOTA PADANG - Marwah, Syafara Hajaratul; Ansofino, Ansofino; Amaluis, Dina (STKIP Pesisir Selatan, 2025)
This study aims to analyze the influence of work discipline, compensation, working hours, and work environment on the performance of Padang City Trade Department employees, both directly and indirectly through work stress as an intervening variable. This type of research is associative with a population of all Padang City Trade Department employees totaling 72 people. The sampling technique uses stratified random sampling. The research instrument is a closed questionnaire. Data analysis uses path analysis and t-test to test the significance of direct and indirect influences between variables. The results of this study indicate that, (1) Directly, work discipline has a significant positive effect on employee performance as indicated by a coefficient of 0.351, this coefficient value is significant because t count is 2.919 ˃ t table 1.66827. Meanwhile, if seen indirectly, work discipline has a negative and significant effect on employee performance through its influence on work stress, this is indicated by a coefficient value of 0.234, this coefficient value is significant because t count is -2.085 ˃ t table 1.66827 (2). Directly, compensation does not have a significant effect on employee performance, as indicated by a coefficient of -0.109. This coefficient value is not significant because the calculated t is -0.802 ˂ 1.66827 t table.